Effect of carbon coating on the electrochemical properties of La–Y–Ni-based hydrogen storage alloys. (10th August 2021) - Wu, Ran; Yuan, Huiping; Liu, Yuru; Hou, Zhenyu; Li, Zhinian; Jiang, Lijun
Abstract: The A2 B7 -type (LaSmY) (NiMnAl)3.5 alloys were prepared by induction melting, and then the alloy samples coated with different contents of nano-carbon were prepared by the mixing and sintering method using pitch as carbon source. The effects of the contents and structure of the coated-carbon on the electrochemical properties of alloy samples were investigated. With the carbon content increase from 0.1 to 1.0 wt%, the cyclic stability is improved and the high-rate dischargeabilitiy (HRD) of the alloy electrodes first increase and then decrease. The kinetic results show that the carbon coating improves the electrocatalytic activity and electrical conductivity of the alloy electrodes. The alloy electrode with 0.5 wt% carbon coating exhibits the best electrochemical properties. The maximum discharge capacity (Cmax ) is 345.7 mAh·g −1, the HRD1200 is 72.49%, and the capacity retention rate (S300 ) is 79.44%. Highlights: The cyclic stability of alloys increased as increased of carbon content. The HRD of alloys first increased and then decreased as increased of carbon content. The alloy with 0.5 wt% carbon coating exhibited the best electrochemical properties. Carbon coating can enhance the electrical conductivity of the alloy. The higher graphitization degree corresponds to the higher electrocatalytic activity.